Character Building Tradition in Maritime Shipping (Study at the Sailing Community in Binongko-Wakatobi Island) - Rudi, La; Hanum, Farida; B. Wahyono, Sugeng (The Pontianak State Institute of Islamic Studies, 2021)
This study aimed to describe the tradition of character building in maritime shipping. The source of the data was the result of ethnographic studies on the sailor community on Binongko Island, Wakatobi Regency. The main instrument in research was researchers, data collection was done through in-depth interviews, participant observation, and document analysis. The results of the study indicated that in the maritime shipping of sailors Binongko-Wakatobi is known for four stages of the character building tradition, namely; (1) providing moral knowledge through prospective sailors; (2) moral inspiration through the role of a koki, (3) moral actions played by sawi; and (4) role models played by juragan. The four stages were interrelated cycles that showed the value of the character's urgency both in maritime shipping. In addition, it is known that the typical character of Binongko sailors who are generally tough, patient, hardworking, unyielding, honest, simple, responsible, and friendly to nature, were formed through the tradition of maritime shipping. Character building interactions occur in oceanic spaces, a means of character building is a traditional boat, while the learning media are marine objects such as; waves, wind and coral.